Rubber material for double-sided vulcanization cross-linking bonding and preparation method thereof

Through the rubber material for double-sided vulcanization cross-linking bonding, the problem of insufficient bonding strength between the ceramic lining plate and the metal frame is solved, and higher bonding strength and grinding efficiency are achieved, avoiding the occurrence of hollowing.

CN119119911APending Publication Date: 2024-12-13ANHUI TEAMPLUS NEW MATERIAL TECH CORP LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410979340.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The bonding strength between the ceramic lining plate and the metal frame is insufficient, resulting in hollowing and incomplete bonding surfaces in mining mills, which affects the grinding efficiency and equipment stability.

Method used

The rubber material for double-sided vulcanized cross-linking bonding is used to improve the mechanical properties and bonding strength of the rubber material through specific ratios and preparation methods, including the use of natural rubber, cis-1,4-polybutadiene rubber, carbon black , sulfur and other raw materials, and stabilized additives such as molybdenum disulfide nanosheets and doped modified molybdenum disulfide powder to improve the uniformity and compatibility of the vulcanization reaction.

Benefits of technology

The bonding strength between the ceramic lining plate and the metal frame is significantly improved, avoiding hollowing on the bonding surface, meeting the requirements for use as an adhesive material, and improving the grinding efficiency and equipment stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004955569660000121
    Figure BDA0004955569660000121
Patent Text Reader

Abstract

The invention discloses a rubber material for double-sided vulcanization crosslinking bonding and a preparation method thereof, and belongs to the technical field of rubber bonding materials, and the rubber material comprises the following components in parts by mass: 180-90 parts of natural rubber RSS, 1-3 parts of cis-1, 3-butanediol, 1-3 parts of a vulcanizing agent, 1-3 parts of a vulcanizing agent and 1-3 parts According to the rubber material, 10-20 parts of 1, 4-polybutadiene rubber, 40-60 parts of carbon black, 1.5-2 parts of sulfur, 0.5-0.6 part of an accelerant, 6-7 parts of zinc oxide, 5-8 parts of a stabilizing auxiliary agent, 1 part of stearic acid, 2 parts of an anti-aging agent, 8 parts of aromatic hydrocarbon oil and 2.5-4 parts of p-tert-butylphenol acetylene resin are used, and the rubber material is used for bonding the ceramic lining plate and the metal framework through double-face vulcanization crosslinking. The mechanical property, the wear resistance and the elasticity of the rubber material are improved, the ceramic lining plate and the metal framework are completely attached, hollowing of a bonding surface is avoided, and the use requirement of the rubber material as a bonding material is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber bonding materials, and in particular relates to a double-sided vulcanized cross-linked bonding rubber material and a preparation method thereof. Background Art

[0002] The mining mill uses internal grinding media (such as steel balls or steel rods, etc.) to impact and grind the raw materials. It is mainly used to grind large pieces of ore into small-sized materials for subsequent ore dressing. The liner is an important consumable in the mining mill. It is generally made of wear-resistant, corrosion-resistant, and high-strength materials. Commonly used materials include cast steel, high manganese steel, ceramics, and rubber.

[0003] As the requirements for energy saving and consumption reduction in various industries increase, it is necessary to improve grinding efficiency and reduce maintenance costs. Liners with excellent performance can reduce friction and wear during the grinding process, and can ensure the stable operation of mining mills, reduce maintenance and replacement costs, thereby improving grinding efficiency and reducing energy consumption. Due to the high wear resistance, corrosion resistance and high temperature resistance of ceramic materials, ceramic liners are increasingly used in mining mill discharge trough products.

[0004] Ceramic linings are generally formed by vulcanizing ceramic sheets and rubber into one piece, and then the ceramic linings are fixed to the metal frame by bolts or cold glue. Due to the limitations of most metal frame structures, conventional bolt fixing cannot be achieved, and cold glue becomes brittle after curing, the bonding surface is not fully fitted, and hollowing is prone to occur. During the use of mining mills, the liner is often impacted and falls off. Therefore, the metal frame and the ceramic lining can be bonded with rubber through vulcanization cross-linking. However, the thermal conductivity of metal materials and ceramic materials is different, and the cooling speed on both sides of the rubber material after vulcanization is uneven, which affects the consistency of the vulcanization degree inside the rubber. Defects such as wrinkles and hollowing may occur, resulting in a decrease in the bonding strength between the ceramic lining and the metal frame. Summary of the invention

[0005] One of the purposes of the present invention is to provide a double-sided vulcanized cross-linked bonding rubber material, to improve the uniformity of the vulcanization reaction of the rubber material, and to increase the bonding strength between the ceramic liner and the metal frame; the second purpose is to provide a preparation method for the double-sided vulcanized cross-linked bonding rubber material.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A double-sided vulcanized cross-linked adhesive rubber material, comprising the following raw materials in parts by mass:

[0008] 180-90 parts of natural rubber RSS, 10-20 parts of cis-1,4-polybutadiene rubber, 40-60 parts of carbon black, 1.5-2 parts of sulfur, 0.5-0.6 parts of accelerator, 6-7 parts of zinc oxide, 5-8 parts of stabilizing agent, 1 part of stearic acid, 2 parts of antioxidant, 8 parts of aromatic oil, and 2.5-4 parts of p-tert-butylphenol acetylene resin.

[0009] Furthermore, the carbon black is one or more of carbon black N660, carbon black N550 and carbon black SP5000A mixed in any ratio.

[0010] Furthermore, the accelerator is a mixture of accelerator CZ and accelerator DM in a mass ratio of 3:10.

[0011] Furthermore, the antioxidant is a mixture of antioxidant 4020 and antioxidant BLE in a mass ratio of 1:1.

[0012] Furthermore, the stabilizing agent is prepared by the following steps:

[0013] Step 1: Add molybdenum disulfide, n-butyl lithium and cyclohexane into a reactor, stir at 300-500 r / min for 10-20 min, then heat to 80-90° C. for hydrothermal reaction for 4-5 h, centrifuge and filter, wash the filter cake with n-hexane 2-3 times, and then ultrasonically disperse with deionized water to form a molybdenum disulfide nanosheet dispersion with a solid content of 0.5%.

[0014] Step 2: Add cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide and molybdenum disulfide nanosheet dispersion into a reactor, ultrasonically disperse for 15-20 minutes, then add 25% ammonia water by mass, hydrothermally react at 100-110° C. for 8-10 hours, centrifuge and filter, wash the filter cake with deionized water for 3-5 times, vacuum dry at 60-80° C., and grind to obtain doped modified molybdenum disulfide powder.

[0015] Step 3: Add the doped modified molybdenum disulfide powder, polyvinyl pyrrolidone and deionized water into a reactor, ultrasonically disperse for 20-30 minutes, adjust the pH value to 8.5-9.5 with ammonia water, and then add styrene monomer, phosphorus-containing acrylate monomer and 1.5% potassium persulfate solution by mass into the reactor under the protection of nitrogen, react for 5-6 hours at 90-95° C. and 500-800 r / min, then add hydrazine hydrate into the reactor, react for 1-1.5 hours under the same conditions, cool naturally, and freeze-dry to obtain a stabilizing agent.

[0016] Furthermore, the usage ratio of molybdenum disulfide, n-butyl lithium and cyclohexane is 1 g: 0.7-0.75 g: 22-25 mL.

[0017] Furthermore, the usage ratio of cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide, molybdenum disulfide nanosheet dispersion and 25% ammonia water is 1.3 g: 0.6 g: 100 mL: 4 mL.

[0018] Furthermore, the dosage ratio of the doped modified molybdenum disulfide powder, polyvinyl pyrrolidone, deionized water, styrene monomer, phosphorus-containing acrylate monomer, potassium persulfate solution and hydrazine hydrate is 0.35-0.38 g: 4.5 g: 320-350 mL: 3.5-4 g: 1-1.9 g: 10 mL: 0.25-0.26 g.

[0019] Further, the phosphorus-containing acrylate monomer is prepared by the following steps:

[0020] Add phenylphosphonyl dichloride and tetrahydrofuran into a reaction kettle and stir to mix; add triethylamine and γ-aminopropylmethyldiethoxysilane at -5°C, stir for 120-150 min at 200-300 r / min, heat to 10-12°C and continue to react for 180-200 min; then add hydroxypropyl acrylate into the reaction kettle, keep stirring at -5°C for 120-150 min, heat to 10-12°C and react for 180-200 min, filter, and rotary evaporate the filtrate to obtain a phosphorus-containing acrylate monomer.

[0021] Furthermore, the usage ratio of phenylphosphonic acid dichloride, tetrahydrofuran, triethylamine, γ-aminopropylmethyldiethoxysilane and hydroxypropyl acrylate is 10-11.7 g: 100-120 mL: 10-12 g: 14-15 g: 5.3-6.1 g.

[0022] A method for preparing a double-sided vulcanized cross-linked adhesive rubber material comprises the following steps:

[0023] Add cis-1,4-polybutadiene rubber into an internal mixer, and plasticize for 50-60 seconds at 80-90°C. Then add natural rubber RSS1, tert-butylphenol acetylene resin and a stabilizing agent, and plasticize for 120-140 seconds at 140-150°C. Then add carbon black and aromatic oil, and mix for 180-210 seconds at 140-160°C. Cool the mixture to 80-85°C after rubber removal. Finally, mix the mixture with sulfur, an accelerator, zinc oxide, stearic acid and an antioxidant, and mix for 160-180 seconds at 90-100°C. Cool the mixture naturally to obtain a double-sided vulcanized cross-linked bonding rubber material.

[0024] Beneficial effects of the present invention:

[0025] The present invention utilizes double-sided vulcanization and cross-linking of rubber materials to bond ceramic lining plates and metal frames, which can ensure the bonding strength of metal frames and ceramic lining plates compared with cold bonding with glue. The rubber material improves the mechanical properties, wear resistance and elasticity of the rubber material through the selection of raw materials and proportions, so that the ceramic lining plates and metal frames are completely bonded, and hollowing of the bonding surface is avoided, thus meeting the use requirements of the bonding material.

[0026] The natural rubber RSS1 and cis-1,4-polybutadiene rubber in the raw materials are compounded to balance the mechanical properties and adhesive properties of the rubber material; carbon black as a reinforcing agent can improve the tensile strength and wear resistance of the rubber material; the addition of tert-butylphenol acetylene resin can improve the adhesion of the rubber material and other materials; the raw material molybdenum disulfide for preparing the stabilizer is treated with n-butyl lithium to peel off the layered molybdenum disulfide into sheets, and then prepared into a dispersion liquid and hydrothermally treated with cerium nitrate hexahydrate to prepare a doped modified molybdenum disulfide powder doped with nano-cerium dioxide, which can be polymerized and coated with a phosphorus-containing acrylate monomer and a styrene monomer to improve the compatibility of the stabilizer and the rubber matrix; the stabilizer can improve the vulcanization uniformity and stability of the rubber material, improve the cross-linking density of the rubber, avoid stress concentration, and avoid defects such as wrinkles and hollows, thereby improving the mechanical properties and peeling strength of the rubber material.

[0027] The phosphorus-containing acrylate monomer contains a phosphate group and an aminosilane group, which can interact with the polar group in the rubber group, help to improve the compatibility of the doped modified molybdenum disulfide powder with the rubber matrix and increase the dispersion performance; the phosphate group can chelate metal ions and improve the peel strength between the rubber material and the metal skeleton through chemical bonding; the aminosilane group can remain stable in a humid or chemically corrosive environment, help to improve the stability of the rubber material, and the aminosilane group can form a strong chemical bond with a variety of substrates, which helps to enhance the adhesion between rubber and other materials. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Embodiment 1: This embodiment provides a double-sided vulcanized cross-linked adhesive rubber material, which is prepared by the following method:

[0030] Step 1: Add 10 kg of molybdenum disulfide, 7 kg of n-butyl lithium and 220 L of cyclohexane into a reactor, stir at 300 r / min for 10 min, then heat to 80 ° C for hydrothermal reaction for 4 h, centrifuge and filter, wash the filter cake twice with n-hexane, and then ultrasonically disperse with deionized water to form a molybdenum disulfide nanosheet dispersion with a solid content of 0.5%.

[0031] Step 2: Add 13 kg of cerium nitrate hexahydrate, 6 kg of hexadecyltrimethylammonium bromide and 1000 L of molybdenum disulfide nanosheet dispersion into a reactor, ultrasonically disperse for 15 minutes, then add 40 L of 25 wt% ammonia water, hydrothermally react at 100 ° C for 8 hours, centrifuge and filter, wash the filter cake with deionized water 3 times, vacuum dry at 60 ° C, and grind to obtain doped modified molybdenum disulfide powder.

[0032] Step 3: Add 10 kg of phenylphosphonic acid dichloride and 100 L of tetrahydrofuran into a reactor and stir to mix, add 10 kg of triethylamine and 14 kg of γ-aminopropylmethyldiethoxysilane at -5 ° C, stir for 120 min at 200 r / min, heat to 10 ° C and continue to react for 180 min, then add 5.3 kg of hydroxypropyl acrylate into the reactor, keep stirring at -5 ° C for 120 min, heat to 10 ° C and react for 180 min, filter, and rotary evaporate the filtrate to obtain a phosphorus-containing acrylate monomer.

[0033] Step 4: Add 3.5 kg of doped modified molybdenum disulfide powder, 45 kg of polyvinyl pyrrolidone and 3200 L of deionized water into the reactor, ultrasonically disperse for 20 minutes, adjust the pH value to 8.5 with ammonia water, and then add 35 kg of styrene monomer, 10 kg of phosphorus-containing acrylate monomer and 100 L of 1.5% potassium persulfate solution into the reactor under the protection of nitrogen, react at 90 ° C and 500 r / min for 5 hours, then add 2.5 kg of hydrazine hydrate into the reactor, react for 1 hour under the same conditions, cool naturally, and freeze-dry to obtain a stabilizing agent.

[0034] Step 5: Add 10kg of cis-1,4-polybutadiene rubber into an internal mixer, plasticize at 80°C for 50s, then add 90kg of natural rubber RSS1, 2.5kg of tert-butylphenol acetylene resin and 5kg of stabilizing agent, plasticize at 140°C for 120s, then add 20kg of carbon black N660, 20kg of carbon black N550 and 8kg of aromatic oil, mix at 140°C for 180s, cool to 80°C, and finally mix with 1.5kg of sulfur, 0.5kg of accelerator, 6kg of zinc oxide, 1kg of stearic acid and 2kg of antioxidant, the accelerator is a mixture of accelerator CZ and accelerator DM in a mass ratio of 3:10, and the antioxidant is a mixture of antioxidant 4020 and antioxidant BLE in a mass ratio of 1:1, mix at 90°C for 160s, cool naturally, and obtain a double-sided vulcanized cross-linking bonding rubber material.

[0035] Embodiment 2: This embodiment provides a double-sided vulcanized cross-linked adhesive rubber material, which is prepared by the following method:

[0036] Step 1: Add 10 kg of molybdenum disulfide, 7.2 kg of n-butyl lithium and 230 L of cyclohexane into a reactor, stir at 350 r / min for 14 min, then heat to 85 ° C for hydrothermal reaction for 4.2 h, centrifuge and filter, wash the filter cake twice with n-hexane, and then ultrasonically disperse with deionized water to form a molybdenum disulfide nanosheet dispersion with a solid content of 0.5%.

[0037] Step 2: Add 13 kg of cerium nitrate hexahydrate, 6 kg of hexadecyltrimethylammonium bromide and 1000 L of molybdenum disulfide nanosheet dispersion into a reactor, ultrasonically disperse for 15 minutes, then add 40 L of 25 wt% ammonia water, hydrothermally react at 100 ° C for 8 hours, centrifuge and filter, wash the filter cake with deionized water 3 times, vacuum dry at 60 ° C, and grind to obtain doped modified molybdenum disulfide powder.

[0038] Step 3: Add 10.5 kg of phenylphosphonic acid dichloride and 105 L of tetrahydrofuran into a reactor and stir to mix, add 10.8 kg of triethylamine and 14.4 kg of γ-aminopropylmethyldiethoxysilane at -5 ° C, stir for 130 min at 250 r / min, heat to 10 ° C and continue to react for 190 min, then add 5.5 kg of hydroxypropyl acrylate into the reactor, keep stirring at -5 ° C for 130 min, heat to 11 ° C and react for 190 min, filter, and rotary evaporate the filtrate to obtain a phosphorus-containing acrylate monomer.

[0039] Step 4: Add 3.6 kg of doped modified molybdenum disulfide powder, 45 kg of polyvinyl pyrrolidone and 3300 L of deionized water into the reactor, ultrasonically disperse for 25 minutes, adjust the pH value to 9 with ammonia water, and then add 37 kg of styrene monomer, 14 kg of phosphorus-containing acrylate monomer and 100 L of 1.5% potassium persulfate solution into the reactor under the protection of nitrogen, react at 92 ° C and 600 r / min for 5.5 hours, then add 2.55 kg of hydrazine hydrate into the reactor, react under the same conditions for 1.2 hours, cool naturally, and freeze-dry to obtain a stabilizing agent.

[0040] Step 5: Add 10kg of cis-1,4-polybutadiene rubber into an internal mixer, plasticize at 80°C for 55s, then add 90kg of natural rubber RSS1, 3kg of tert-butylphenol acetylene resin and 6kg of stabilizing agent, plasticize at 145°C for 130s, then add 30kg of carbon black N660, 20kg of carbon black N550 and 8kg of aromatic oil, mix at 150°C for 190s, cool to 82°C, and finally mix with 1.8kg of sulfur, 0.55kg of accelerator, 6.5kg of zinc oxide, 1kg of stearic acid and 2kg of antioxidant, the accelerator is a mixture of accelerator CZ and accelerator DM in a mass ratio of 3:10, and the antioxidant is a mixture of antioxidant 4020 and antioxidant BLE in a mass ratio of 1:1, mix at 95°C for 170s, cool naturally, and obtain a double-sided vulcanized cross-linked bonding rubber material.

[0041] Embodiment 3: This embodiment provides a double-sided vulcanized cross-linked adhesive rubber material, which is prepared by the following method:

[0042] Step 1: Add 10 kg of molybdenum disulfide, 7.2 kg of n-butyl lithium and 235 L of cyclohexane into a reactor, stir at 400 r / min for 15 min, then heat to 85 ° C for hydrothermal reaction for 4.5 h, centrifuge and filter, wash the filter cake twice with n-hexane, and then ultrasonically disperse with deionized water to form a molybdenum disulfide nanosheet dispersion with a solid content of 0.5%.

[0043] Step 2: Add 13 kg of cerium nitrate hexahydrate, 6 kg of hexadecyltrimethylammonium bromide and 1000 L of molybdenum disulfide nanosheet dispersion into a reactor, ultrasonically disperse for 18 minutes, then add 40 L of 25 wt% ammonia water, hydrothermally react at 105 ° C for 9 hours, centrifuge and filter, wash the filter cake with deionized water 4 times, vacuum dry at 70 ° C, and grind to obtain doped modified molybdenum disulfide powder.

[0044] Step 3: Add 11.2 kg of phenylphosphonic acid dichloride and 110 L of tetrahydrofuran into a reactor and stir to mix, add 11 kg of triethylamine and 14.5 kg of γ-aminopropylmethyldiethoxysilane at -5 ° C, stir for 135 min at 250 r / min, heat to 10-12 ° C and continue to react for 190 min, then add 5.7 kg of hydroxypropyl acrylate into the reactor, keep stirring at -5 ° C for 140 min, heat to 11 ° C and react for 190 min, filter, and rotary evaporate the filtrate to obtain a phosphorus-containing acrylate monomer.

[0045] Step 4: Add 3.7 kg of doped modified molybdenum disulfide powder, 45 kg of polyvinyl pyrrolidone and 3400 L of deionized water into the reactor, ultrasonically disperse for 25 minutes, adjust the pH value to 9 with ammonia water, and then add 38 kg of styrene monomer, 15 kg of phosphorus-containing acrylate monomer and 100 L of 1.5% potassium persulfate solution into the reactor under the protection of nitrogen, react at 93 ° C and 650 r / min for 5.5 hours, then add 2.55 kg of hydrazine hydrate into the reactor, react under the same conditions for 1.3 hours, cool naturally, and freeze-dry to obtain a stabilizing agent.

[0046] Step 5: Add 15kg of cis-1,4-polybutadiene rubber into an internal mixer, plasticize at 85°C for 55s, then add 90kg of natural rubber RSS1, 3kg of tert-butylphenol acetylene resin and 7kg of stabilizing agent, plasticize at 15°C for 130s, then add 20kg of carbon black N660, 30kg of carbon black N550 and 8kg of aromatic oil, mix at 150°C for 200s, cool to 83°C, and finally mix with 1.8kg of sulfur, 0.6kg of accelerator, 6.8kg of zinc oxide, 1kg of stearic acid and 2kg of antioxidant, the accelerator is a mixture of accelerator CZ and accelerator DM in a mass ratio of 3:10, and the antioxidant is a mixture of antioxidant 4020 and antioxidant BLE in a mass ratio of 1:1, mix at 95°C for 170s, cool naturally, and obtain a double-sided vulcanized cross-linked bonding rubber material.

[0047] Embodiment 4: This embodiment provides a double-sided vulcanized cross-linked adhesive rubber material, which is prepared by the following method:

[0048] Step 1: Add 10 kg of molybdenum disulfide, 7.3 kg of n-butyl lithium and 240 L of cyclohexane into a reactor, stir at 450 r / min for 15 min, then heat to 85 ° C for hydrothermal reaction for 4.5 h, centrifuge and filter, wash the filter cake with n-hexane for 3 times, and then ultrasonically disperse with deionized water to form a molybdenum disulfide nanosheet dispersion with a solid content of 0.5%.

[0049] Step 2: Add 13 kg of cerium nitrate hexahydrate, 6 kg of hexadecyltrimethylammonium bromide and 1000 L of molybdenum disulfide nanosheet dispersion into a reactor, ultrasonically disperse for 20 minutes, then add 40 L of 25 wt% ammonia water, hydrothermally react at 110° C. for 10 hours, centrifuge and filter, wash the filter cake with deionized water 5 times, vacuum dry at 80° C., and grind to obtain doped modified molybdenum disulfide powder.

[0050] Step 3: Add 11.7 kg of phenylphosphonic acid dichloride and 120 L of tetrahydrofuran into a reactor and stir to mix, add 12 kg of triethylamine and 15 kg of γ-aminopropylmethyldiethoxysilane at -5 ° C, stir for 150 min at 300 r / min, heat to 12 ° C and continue to react for 200 min, then add 6.1 kg of hydroxypropyl acrylate into the reactor, keep stirring at -5 ° C for 150 min, heat to 12 ° C and react for 200 min, filter, and rotary evaporate the filtrate to obtain a phosphorus-containing acrylate monomer.

[0051] Step 4: Add 3.7 kg of doped modified molybdenum disulfide powder, 45 kg of polyvinyl pyrrolidone and 3400 L of deionized water into the reactor, ultrasonically disperse for 25 minutes, adjust the pH value to 9 with ammonia water, and then add 40 kg of styrene monomer, 19 kg of phosphorus-containing acrylate monomer and 100 L of 1.5% potassium persulfate solution into the reactor under the protection of nitrogen, react at 95 ° C and 700 r / min for 6 hours, then add 2.6 kg of hydrazine hydrate into the reactor, react under the same conditions for 1.5 hours, cool naturally, and freeze-dry to obtain a stabilizing agent.

[0052] Step 5: Add 15kg of cis-1,4-polybutadiene rubber into an internal mixer, and plasticize at 90°C for 60s. Then add 90kg of natural rubber RSS1, 3.5kg of tert-butylphenol acetylene resin and 8kg of stabilizing agent, and plasticize at 150°C for 140s. Then add 20kg of carbon black N660, 25kg of carbon black N550, 10kg of carbon black SP5000A and 8kg of aromatic oil, and mix at 160°C. After refining for 210 seconds, the rubber was discharged and cooled to 85°C, and finally mixed with 2kg of sulfur, 0.6kg of accelerator, 7kg of zinc oxide, 1kg of stearic acid and 2kg of antioxidant. The accelerator was a mixture of accelerator CZ and accelerator DM in a mass ratio of 3:10, and the antioxidant was a mixture of antioxidant 4020 and antioxidant BLE in a mass ratio of 1:1. The rubber was mixed at 100°C for 180 seconds and cooled naturally to obtain a double-sided vulcanized cross-linked bonding rubber material.

[0053] Embodiment 5: This embodiment provides a double-sided vulcanized cross-linked adhesive rubber material, which is prepared by the following method:

[0054] Step 1: Add 10 kg of molybdenum disulfide, 7.5 kg of n-butyl lithium and 250 L of cyclohexane into a reactor, stir at 500 r / min for 20 min, then heat to 90 ° C for hydrothermal reaction for 5 h, centrifuge and filter, wash the filter cake with n-hexane for 3 times, and then use deionized water to ultrasonically disperse it into a molybdenum disulfide nanosheet dispersion with a solid content of 0.5%.

[0055] Step 2: Add 13 kg of cerium nitrate hexahydrate, 6 kg of hexadecyltrimethylammonium bromide and 1000 L of molybdenum disulfide nanosheet dispersion into a reactor, ultrasonically disperse for 20 minutes, then add 40 L of 25 wt% ammonia water, hydrothermally react at 110° C. for 10 hours, centrifuge and filter, wash the filter cake with deionized water 5 times, vacuum dry at 80° C., and grind to obtain doped modified molybdenum disulfide powder.

[0056] Step 3: Add 11.7 kg of phenylphosphonic acid dichloride and 120 L of tetrahydrofuran into a reactor and stir to mix, add 12 kg of triethylamine and 15 kg of γ-aminopropylmethyldiethoxysilane at -5 ° C, stir for 150 min at 300 r / min, heat to 12 ° C and continue to react for 200 min, then add 6.1 kg of hydroxypropyl acrylate into the reactor, keep stirring at -5 ° C for 150 min, heat to 12 ° C and react for 200 min, filter, and rotary evaporate the filtrate to obtain a phosphorus-containing acrylate monomer.

[0057] Step 4: Add 3.8 kg of doped modified molybdenum disulfide powder, 45 kg of polyvinyl pyrrolidone and 3500 L of deionized water into the reactor, ultrasonically disperse for 30 minutes, adjust the pH value to 9.5 with ammonia water, and then add 40 kg of styrene monomer, 19 kg of phosphorus-containing acrylate monomer and 100 L of 1.5% potassium persulfate solution into the reactor under the protection of nitrogen, react at 95 ° C and 800 r / min for 6 hours, then add 2.6 kg of hydrazine hydrate into the reactor, react under the same conditions for 1.5 hours, cool naturally, and freeze-dry to obtain a stabilizing agent.

[0058] Step 5: Add 20kg of cis-1,4-polybutadiene rubber into an internal mixer, and plasticize at 90°C for 60s. Then add 80kg of natural rubber RSS1, 4kg of tert-butylphenol acetylene resin and 8kg of stabilizing agent, and plasticize at 150°C for 140s. Then add 25kg of carbon black N660, 25kg of carbon black N550, 10kg of carbon black SP5000A and 8kg of aromatic oil, and mix at 160°C. After refining for 210 seconds, the rubber was discharged and cooled to 85°C, and finally mixed with 2kg of sulfur, 0.6kg of accelerator, 7kg of zinc oxide, 1kg of stearic acid and 2kg of antioxidant. The accelerator was a mixture of accelerator CZ and accelerator DM in a mass ratio of 3:10, and the antioxidant was a mixture of antioxidant 4020 and antioxidant BLE in a mass ratio of 1:1. The rubber was mixed at 100°C for 180 seconds and cooled naturally to obtain a double-sided vulcanized cross-linked bonding rubber material.

[0059] Comparative Example 1: Based on Example 4, the stabilizing agent was replaced with the raw material molybdenum disulfide, and the other steps remained unchanged to prepare a rubber material.

[0060] Comparative Example 2: Based on Example 4, the stabilizing agent was replaced with doped modified molybdenum disulfide powder, and the other steps remained unchanged to prepare a rubber material.

[0061] Comparative Example 3: Based on Example 4, the doped modified molybdenum disulfide powder in step 4 was replaced with raw molybdenum disulfide, and the other steps remained unchanged to prepare a rubber material.

[0062] Comparative Example 4: Based on Example 4, the phosphorus-containing acrylate monomer in step 4 is replaced with a styrene monomer of the same mass, and the remaining steps remain unchanged to prepare a rubber material.

[0063] In the examples and comparative examples, cis-1,4-polybutadiene rubber was purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.; p-tert-butylphenol acetylene resin was purchased from Wuhan Rongcan Biotechnology Co., Ltd., with the product number acetylene resin 208; the brand of carbon black was Cabot; and aromatic oil was purchased from Suzhou Senfida Chemical Co., Ltd.

[0064] Performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 4. Different samples were prepared according to the corresponding standards. The vulcanization conditions of the samples were 185KGF, 140°C vulcanization for 170 min, and 130°C vulcanization for 100 min. With reference to GB / T 528-2009, the tensile strength, elongation at break and 100% tensile strength of the tensile samples were tested using an electronic tensile testing machine; with reference to GB / T 7760-2003, the peel strength of different samples was tested, and the hard plates were tinplate and alumina ceramic plates; with reference to GB / T 1681-2009, the rubber elasticity of different samples was tested; with reference to GBT 1689-2014, the AKRON abrasion test was performed to test the abrasion of different samples.

[0065] The results are shown in Table 1:

[0066] Table 1

[0067]

[0068] It can be seen from Table 1 that the rubber materials in Examples 1 to 4 have better mechanical properties, and the peel strengths between the rubber materials and the tinplate plate and the alumina ceramic plate are higher than those in Comparative Examples 1 to 3, because molybdenum disulfide doped with cerium oxide can improve the vulcanization performance of the rubber material, increase the crosslinking density of the rubber, and thus improve the mechanical properties and peel strength of the rubber material; Comparative Example 4 shows that adding phosphorus-containing acrylate when preparing the stabilizing agent can improve the peel strength between the rubber material and the tinplate plate, because the phosphorus-containing groups contained therein can chelate metal ions, thereby improving the peel strength between the rubber material and the metal substrate through chemical bonding.

[0069] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A double-sided vulcanized cross-linked adhesive rubber material, characterized in that: The following raw materials are included by mass: Natural rubber RSS1 80-90 parts, cis-1,4-polybutadiene rubber 10-20 parts, carbon black 40-60 parts, sulfur 1.5-2 parts, accelerator 0.5-0.6 parts, zinc oxide 6-7 parts, stabilizer 5-8 parts, stearic acid 1 part, antioxidant 2 parts, aromatic oil 8 parts, tert-butylphenol acetylene resin 2.5-4 parts; The stabilizing agent is prepared by the following steps: Doped modified molybdenum disulfide powder, polyvinyl pyrrolidone and deionized water are added to a reactor, ultrasonically dispersed for 20-30 minutes, the pH value is adjusted to 8.5-9.5 with ammonia water, and then styrene monomer, phosphorus-containing acrylate monomer and 1.5% potassium persulfate solution by mass are added to the reactor under the protection of nitrogen, and reacted for 5-6 hours at 90-95° C. and 500-800 r / min, and then hydrazine hydrate is added to the reactor, reacted for 1-1.5 hours under the same conditions, naturally cooled, and freeze-dried to obtain a stabilizing additive.

2. A double-sided vulcanized cross-linked adhesive rubber material according to claim 1, characterized in that: The dosage ratio of the doped modified molybdenum disulfide powder, polyvinyl pyrrolidone, deionized water, styrene monomer, phosphorus-containing acrylate monomer, potassium persulfate solution and hydrazine hydrate is 0.35-0.38 g: 4.5 g: 320-350 mL: 3.5-4 g: 1-1.9 g: 10 mL: 0.25-0.26 g.

3. The double-sided vulcanized cross-linked adhesive rubber material according to claim 1, characterized in that: The carbon black is one or more of carbon black N660, carbon black N550 and carbon black SP5000A mixed in any ratio.

4. The double-sided vulcanized cross-linked adhesive rubber material according to claim 1, characterized in that: The accelerator is a mixture of accelerator CZ and accelerator DM in a mass ratio of 3:

10.

5. The double-sided vulcanized cross-linked adhesive rubber material according to claim 1, characterized in that: The antioxidant is a mixture of antioxidant 4020 and antioxidant BLE in a mass ratio of 1:

1.

6. The double-sided vulcanized cross-linked adhesive rubber material according to claim 1, characterized in that: The doped and modified molybdenum disulfide powder is prepared by the following steps: Cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide and molybdenum disulfide nanosheet dispersion are added to a reaction kettle, ultrasonically dispersed for 15-20 minutes, then 25wt% ammonia water is added, hydrothermally reacted at 100-110°C for 8-10 hours, centrifuged and filtered, the filter cake is washed with deionized water for 3-5 times, vacuum dried at 60-80°C, and ground to obtain doped modified molybdenum disulfide powder; the dosage ratio of the cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide, molybdenum disulfide nanosheet dispersion and 25% ammonia water is 1.3g:0.6g:100mL:4mL.

7. A double-sided vulcanized cross-linked adhesive rubber material according to claim 6, characterized in that: The molybdenum disulfide nanosheet dispersion is prepared by the following steps: Molybdenum disulfide, n-butyl lithium and cyclohexane are added into a reactor in a dosage ratio of 1 g: 0.7-0.75 g: 22-25 mL, stirred at 300-500 r / min for 10-20 min, hydrothermally reacted at 80-90° C. for 4-5 h, centrifuged and filtered, the filter cake is washed with n-hexane for 2-3 times, and then ultrasonically dispersed with deionized water to form a molybdenum disulfide nanosheet dispersion with a solid content of 0.5%.

8. The double-sided vulcanized cross-linked adhesive rubber material according to claim 1, characterized in that: The phosphorus-containing acrylate monomer is prepared by the following steps: Add phenylphosphonyl dichloride and tetrahydrofuran into a reaction kettle and stir to mix; add triethylamine and γ-aminopropylmethyldiethoxysilane at -5°C, stir for 120-150 min at 200-300 r / min, heat to 10-12°C and continue to react for 180-200 min; then add hydroxypropyl acrylate into the reaction kettle, keep stirring at -5°C for 120-150 min, heat to 10-12°C and react for 180-200 min, filter, and rotary evaporate the filtrate to obtain a phosphorus-containing acrylate monomer.

9. The double-sided vulcanized cross-linked adhesive rubber material according to claim 8, characterized in that: The usage ratio of phenylphosphonic acid dichloride, tetrahydrofuran, triethylamine, γ-aminopropylmethyldiethoxysilane and hydroxypropyl acrylate is 10-11.7g: 100-120mL: 10-12g: 14-15g: 5.3-6.1g.

10. The method for preparing a double-sided vulcanized cross-linked adhesive rubber material according to claim 1, characterized in that: The steps include: Add cis-1,4-polybutadiene rubber into an internal mixer, and plasticize for 50-60 seconds at 80-90°C. Then add natural rubber RSS1, tert-butylphenol acetylene resin and a stabilizing agent, and plasticize for 120-140 seconds at 140-150°C. Then add carbon black and aromatic oil, and mix for 180-210 seconds at 140-160°C. Cool the mixture to 80-85°C after rubber removal. Finally, mix the mixture with sulfur, an accelerator, zinc oxide, stearic acid and an antioxidant, and mix for 160-180 seconds at 90-100°C. Cool the mixture naturally to obtain a double-sided vulcanized cross-linked bonding rubber material.

Citation Information

Cited By

  • Polypropylene insulating material for bipolar coagulation forceps and preparation method of polypropylene insulating material

    CN121306691A